Relationship between impression management strategies and social relationship dimensions amongst Mardam-Bey's internet relay chat users - Attan, Sri Azra (2011)
Impression management is a process by which individuals attempt to control the perception from others, and it is pervasive in social interaction. However, managing impressions online through Mardam-Bey’s Internet Relay Chat (mIRC), which is a text tbased chat application, requires more effort in the cyber community, since it is not as the same as in Face-to-Face (FtF) interaction. mIRC users need to improve the skill of using impression management strategies namely demonstrating mastery, managing similarity, using nickname and misrepresentation identity to replace the element of emotion, posture, gesture and the behaviour of verbal and non-verbal communication in order to develop the social relationships amongst them. Thus, the study was examining the relationship between impression management strategies and social relationship development amongst mIRC users in the mIRC through social relationship dimensions namely emotional loneliness, emotional closeness and self-esteem. A quantitative survey was conducted by distributing a set of a questionnaire via email to 202 mIRC users who were selected through a random sampling technique. The findings revealed that most of the correlations between impression management strategies and social relationship dimensions amongst mIRC users were positive. However, not all of the correlations were significant. There was a positive significant correlation between managing similarity and emotional loneliness, emotional closeness along with selfesteem. There was also a positive significant correlation between demonstrating mastery, using nickname and misrepresentation identity with emotional closeness. Nonetheless, there was no significant correlation between demonstrating mastery, using nickname and misrepresentation identity with emotional loneliness and self-esteem. As a conclusion, there are no differences between Computer-Mediated Communication (CMC) and FtF interaction, since Internet users are not depending on FtF only to develop the social relationship because they by now are utilizing another alternative through CMC such as mIRC to get friends in the cyber community.